Environmental and anthropogenic factors synergistically affect space use of jaguars - Thompson, Jeffrey J.; Morato, Ronaldo G.; Niebuhr, Bernardo B. [UNESP]; Alegre, Vanesa Bejarano [UNESP]; Oshima, Júlia Emi F. [UNESP]; de Barros, Alan E.; Paviolo, Agustín; de la Torre, J. Antonio; Lima, Fernando [UNESP]; McBride, Roy T.; Cunha de Paula, Rogerio; Cullen, Laury; et al. (Elsevier, 2021)
Large terrestrial carnivores have undergone some of the largest population declines and range reductions of any species, which is of concern as they can have large effects on ecosystem dynamics and function.1–4 The jaguar (Panthera onca) is the apex predator throughout the majority of the Neotropics; however, its distribution has been reduced by >50% and it survives in increasingly isolated populations.5 Consequently, the range-wide management of the jaguar depends upon maintaining core populations connected through multi-national, transboundary cooperation, which requires understanding the movement ecology and space use of jaguars throughout their range.6–8 Using GPS telemetry data for 111 jaguars from 13 ecoregions within the four biomes that constitute the majority of jaguar habitat, we examined the landscape-level environmental and anthropogenic factors related to jaguar home range size and movement parameters. Home range size decreased with increasing net productivity and forest cover and increased with increasing road density. Speed decreased with increasing forest cover with no sexual differences, while males had more directional movements, but tortuosity in movements was not related to any landscape factors. We demonstrated a synergistic relationship between landscape-scale environmental and anthropogenic factors and jaguars’ spatial needs, which has applications to the conservation strategy for the species throughout the Neotropics. Using large-scale collaboration, we overcame limitations from small sample sizes typical in large carnivore research to provide a mechanism to evaluate habitat quality for jaguars and an inferential modeling framework adaptable to the conservation of other large terrestrial carnivores.
Keywords: AKDE; carnivore; home range; jaguar; landscape factors; movement ecology; Neotropics; Panthera onca; speed; telemetry